2006
DOI: 10.1037/0021-843x.115.3.580
|View full text |Cite
|
Sign up to set email alerts
|

Phylo- and ontogenetic fears and the expectation of danger: Differences between spider- and flight-phobic subjects in cognitive and physiological responses to disorder-specific stimuli.

Abstract: To compare specific phobias with an assumed phylogenetic or ontogenetic origin in responses to fear-relevant (FR) stimuli, 17 spider-and 17 flight-phobic participants were exposed to pictures of spiders, flight accidents, or mushrooms randomly followed by either a startling noise or nothing else. While both groups showed a disorder-specific expectancy bias, only spider-phobic participants exhibited a disorder-specific covariation bias. Spider-phobic participants also showed enhanced skin conductance responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 44 publications
5
59
0
1
Order By: Relevance
“…Spider fearful individuals tended to falsely recall more spider-related words than neutral words (words that had not actually been presented before). On the other hand, the Mühlberger et al (2006) study with spider and flight phobics did not reveal any difference in picture frequency estimates for phobic versus nonphobic content.…”
Section: Evidence For An Encounter Expectancy Bias In Fear Of Spidersmentioning
confidence: 58%
See 2 more Smart Citations
“…Spider fearful individuals tended to falsely recall more spider-related words than neutral words (words that had not actually been presented before). On the other hand, the Mühlberger et al (2006) study with spider and flight phobics did not reveal any difference in picture frequency estimates for phobic versus nonphobic content.…”
Section: Evidence For An Encounter Expectancy Bias In Fear Of Spidersmentioning
confidence: 58%
“…Interestingly this overestimation was limited to phylogenetic threat stimuli and was not obtained with ontogenetic threat stimuli such as weapons (de Jong et al, 1992). Mühlberger, Wiedemann, Herrmann, and Pauli (2006) showed that the a priori expectancy bias did not differ between phylogenetic phobia (spider phobia) and ontogenetic phobia (flight phobia). Both spider phobics and flight phobics exhibited an overestimation of the likelihood that their particularly feared type of threat would be Encounter expectancy bias in fear of spiders 4 followed by a startling white noise (cf.…”
Section: Evidence For An Encounter Expectancy Bias In Fear Of Spidersmentioning
confidence: 88%
See 1 more Smart Citation
“…(3) Converging evidence points toward a crucial role of unflexible and maladaptive processing of emotional stimuli in the pathogenesis of anxiety and anxiety disorders: anxiety-related emotional stimuli are rated as more threatening by patients than by control individuals and seem to be processed differently within the limbic-medial prefrontal circuit, partly driven by genetic factors (eg, Domschke et al, 2006Domschke et al, , 2008bDomschke and Dannlowski, 2010;Etkin, 2010;Lang and Cuthbert, 1984;Mathews, 1993;Mühlberger et al, 2006Mühlberger et al, , 2007Pauli et al, 1996;Wiedemann et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Here too, there is some inconsistency among investigators. While some studies found no differences between the two types of stimuli (Davey, 1995;Davey & Craigie, 1997;Davey & Dixon, 1996;Honeybourne, Matchett, & Davey, 1993;Lovibond, Siddle, & Bond, 1993), others reported that both arousal and conditioning are more intense to phylogenic fear-relevant stimuli than to ontogenetic fear-relevant stimuli (Mühlberger, Wiedemann, Herrmann, & Pauli, 2006;Öhman & Mineka, 2001). Findings also show that fear-relevant stimuli capture subjects' attention and are perceived more rapidly than fear-irrelevant stimuli (Öhman, Flykt, & Esteves, 2001;Waters & Lipp, 2008).…”
Section: Preparedness Theorymentioning
confidence: 94%